2013
DOI: 10.1002/app.39522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bamboo charcoal powder on the curing characteristics, mechanical properties, and thermal properties of styrene–butadiene rubber with bamboo charcoal powder

Abstract: Compounds of styrene-butadiene rubber (SBR) filled with bamboo charcoal powders (BCPs) were prepared with a laboratory-sized two-roll mill. The effects of the BCP loading on the curing characteristics and mechanical and thermal properties were investigated. The results indicate that the addition of BCP resulted in a longer curing time and a higher Mooney viscosity in the SBR materials. The incorporation of BCP into SBR improved the mechanical properties and dynamic properties. Furthermore, the mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 59 publications
4
18
0
1
Order By: Relevance
“…The vulcanization characteristics expressed in terms of the difference of minimum and maximum torque value, Δ H = ( M H − M L ), scorch time, t S2 , optimum cure time, t 90 are reported in Table . It is observed that the difference of minimum and maximum torque value reflecting the degree of crosslink increased significantly with the growing loading of RBC, which may be attributed to that the inclusion of rigid and hard RBC into soft rubber matrix tends to immobilize the movement of macromolecular rubber chains . In addition, when more RBC was incorporated, the scorch time t s2 lowed down, as well as the curing time.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The vulcanization characteristics expressed in terms of the difference of minimum and maximum torque value, Δ H = ( M H − M L ), scorch time, t S2 , optimum cure time, t 90 are reported in Table . It is observed that the difference of minimum and maximum torque value reflecting the degree of crosslink increased significantly with the growing loading of RBC, which may be attributed to that the inclusion of rigid and hard RBC into soft rubber matrix tends to immobilize the movement of macromolecular rubber chains . In addition, when more RBC was incorporated, the scorch time t s2 lowed down, as well as the curing time.…”
Section: Resultsmentioning
confidence: 96%
“…c and d, respectively. Generally, the thermal stability of the compounds versus the filler loading are positive or negative correlation, such as bamboo charcoal powers/styrene–butadiene rubber , polyethylene/carbon nanotube composites , poly(ε‐caprolactone)/clay nanocomposites . However, in our study, whether in nitrogen or in air condition, the decomposition temperatures of the composites reached to a maximum at 40 phr and then shifted slightly lower with increased loading.…”
Section: Resultsmentioning
confidence: 99%
“…The curing properties of the samples were determined on a rotorless rubber curometer (RC2000E) at 145°C for 40 min. The cure rate index (CRI) was determined from the curing curve using the following formula : CRI=100(T90ts2), where t s2 is the scorch time and T 90 is the curing time.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, biochar, a product from biomass thermochemical conversion, has received increasing attention for use as a polymer filler. It is a renewable and inexpensive material, which possesses many advantages, such as having a high surface area and high carbon content, having good thermal stability, possessing good electrical conductivity, being a supplier of negative ions, and having a warming effect of far infrared rays . Owing to these advantages, pyrolysis biochar could potentially find its way into the novel biochar–polymer composites.…”
Section: Introductionmentioning
confidence: 99%